Pengaruh Hijabers Community Terhadap Gaya Hidup Dan Keputusan Pembelian Hijab Pada Mahasiswa Fakultas Ekonomi Universitas Jember - Riskiyana Ulfa; Deasy Wulandari; N. Ari Subagio (e-Journal Ekonomi Bisnis dan Akuntansi, 2014)
his study aims to identify and analyze significant effect on the Hijabers community through lifestyle, identify and analyze significant influence on lifestyle through hijab purchasing decisions , identify and analyze significant effect on the hijabers community through hijab purchasing decisions at Economics Faculty's students of Jember University. This research is an explanatory research. The population of this study were female students and wear hijab at the Faculty of Economics, University of Jember. Selected sample of 100 respondents, sampling technique using convenience sampling. Methods of data analysis using Structural Equation Modeling (SEM) . The results of the study showed that hijabers community significant influence on lifestyle, lifestyle significantly influence purchasing decisions hijab and hijabers community significantly influence hijab purchasing decisions at Economics Faculty's students of Jember University.